The Exhaust Emission Characteristics of a Spark-Ignition Engine Fuelled with Gasoline and Synthesized Biogas from Non-Thermal Plasma - Tzeng, L.M. (IOP Publishing Ltd, 2021)
This study synthesizes biogas with low methane contents (<50) to hydrocarbons that form a combustible synthesis gas (syngas) mixture. Conventional methods used for reforming biogas has limitations in terms of fabrication, maintenance, and cost. This is especially true when the biogas' composition fluctuates. Non-thermal plasma (NTP) is an alternative method to produce combustible syngas for power generation. Thus, the exhaust emissions from a 2 kWe spark ignition (SI) engine fuelled with gasoline and NTP-synthesized biogas is investigated with respect to the type of NTP reactor, plasma power consumption and biogas composition. Two types of NTP reactors are used: a cylindrical reactor where the gas flow path is linear, and a cyclonic reactor where the gas flow path is a curvature, similar to that of a gas-solid cyclone separator. The results show that the NTP reactors produced additional hydrocarbons, decreasing flue gas temperatures by 4 C and reducing NOx emissions by 35. Â© Published under licence by IOP Publishing Ltd.